Return to sport after lumbar disc herniation surgery: a narrative review of surgical techniques, rehabilitation, and outcomes - Korowaj, Karolina; Gadzielik, Aleksandra; Papciak, Kinga Zofia; Dercz, Maciej Piotr; Woźniak, Klaudia; Palacz, Jakub Paweł; Fitas, Alicja; Radliński, Michał; Jabłońska, Urszula Zofia; Głaszczka, Michał (Quality in Sport, 2026)
Background. Lumbar disc herniation (LDH) is prevalent among elite athletes, reaching up to 75% in high-impact sports. Extreme physical demands accelerate spinal degeneration, making the choice between surgical and conservative management critical for rapid return to play (RTP). Aim. This review evaluates the impact of surgical techniques, phased rehabilitation, and sport-specific factors on RTS rates and timing after surgery. Material and methods. A qualitative synthesis of 23 sources was performed, including meta-analyses, systematic reviews, and league-specific cohort studies. Results. RTS rates after discectomy are high (75%–100%). Minimally invasive procedures, particularly transforaminal endoscopic discectomy (TELD), offer shorter recovery times (avg. 4 months) and less back pain than microdiscectomy. Recovery is optimized through structured, four-phase rehabilitation focusing on core stabilization and "hip hinge" motor control. While surgery provides faster short-term relief, long-term functional outcomes often align with conservative management. Conclusions. Surgery effectively enables rapid symptom resolution in elite athletes. Long-term success depends on adherence to phased rehabilitation. Endoscopic techniques represent a promising advancement in reducing morbidity and shortening recovery time in the athletic population.